Decentralized substations for low-temperature district heating with no Legionella risk, and low return temperatures. (1st September 2016) - Yang, Xiaochen; Li, Hongwei; Svendsen, Svend
Abstract: To improve energy efficiency and give more access to renewable energy sources, low-temperature district heating (LTDH) is a promising concept to be realized in the future. However, concern about Legionella proliferation restricts applying low-temperature district heating in conventional systems with domestic hot water (DHW) circulation. In this study, a system with decentralized substations was analysed as a solution to this problem. Furthermore, a modification for the decentralized substation system were proposed in order to reduce the average return temperature. Models of conventional system with medium-temperature district heating, decentralized substation system with LTDH, and innovative decentralized substation system with LTDH were built based on the information of a case building. The annual distribution heat loss and the operating costs of the three scenarios were calculated and compared. From the results, realizing LTDH by the decentralized substation unit, 30% of the annual distribution heat loss inside the building can be saved compared to a conventional system with medium-temperature district heating. Replacing the bypass pipe with an in-line supply pipe and a heat pump, the innovative decentralized substation system can reduce distribution heat loss by 39% compared to the conventional system and by 12% compared to the normal decentralized substation system with bypass. Highlights: The system of decentralized substations can realize low-temperature district heating without running the risk of Legionella. Decentralized substations help reduce the distribution heat loss inside the building compared to conventional system. A new concept that can reduce the return temperature for district heating is proposed and analysed.